The Relationship Between Dietary Patterns, Physical Activity, and Stress Levels with the Incidence of Hypertension among Adults of Productive Age - Vandika, Danuartha; Maliya, Arina (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Hypertension is a major public health concern among productive-age individuals, influenced not only by genetic factors but also by modifiable lifestyle factors such as diet, physical activity, and stress. Objective: This study aimed to analyze the relationship between diet, physical activity, and stress levels with the incidence of hypertension among individuals in the productive age group. Methods: A quantitative research design with a Cross-Sectional approach was employed using purposive sampling involving 112 hypertensive respondents of productive age, and data were analyzed using the Spearman-Rho correlation test. Results: The findings revealed a significant positive relationship between dietary patterns and hypertension incidence (p = 0.001). More than half of the respondents engaged in light physical activity, and a positive correlation was observed between physical activity and hypertension (p = 0.001). Additionally, stress levels were significantly correlated with hypertension incidence (p = 0.001). These results indicate that poor dietary adherence, low physical activity, and high stress levels contribute to the increasing prevalence of hypertension among productive-age adults. Conclusion: Maintaining a balanced diet, engaging in regular physical activity, and managing stress effectively are crucial strategies to prevent hypertension and promote cardiovascular health in the productive age population.